Copy Number Variation Analysis of 5p Deletion Provides Accurate Prenatal Diagnosis and Reveals Candidate Pathogenic Genes - Chu, Guoming; Li, Pingping; Wen, Juan; Zheng, Gaoyan; Zhao, Yanyan; He, Rong (Frontiers in Medicine, 2022)
Objective: 5p deletion syndrome, that characterized by cat-like cry and peculiar timbre of voice, is believed to be one of the most common pathogenic copy number variations (CNVs). Variable critical regions on 5p involving a variety of genes contribute to the phenotypic heterogeneity without specific correlation. The objective of this study was to examine the genotype-phenotype correlation of 5p deletion syndrome, and to redefine 5p deletion syndrome relevant regions. In addition, we demonstrate the potential use of whole genome sequencing (WGS) to identify chromosomal breakpoints in prenatal diagnosis. Methods: Three families with women undergoing prenatal diagnosis and two children were recruited. Karyotyping, CNV-seq, fluorescence in situ hybridization, WGS, and Sanger sequencing were performed to identify the chromosomal disorder. Results: We reported three families and two children with CNVs of 5p deletion or combined 6p duplication. Five different sizes of 5p deletion were detected and their pathogenicity was determined, including 5p15.33-p15.31 [1-7,700,000, family1-variant of uncertain significance (VUS)], 5p15.33 (1-3,220,000, family 2-VUS), 5p15.33-p15.31 (1-7,040,000, family 3-VUS), 5p15.33-p15.31 (1-8,740,000, child 1-pathogenic) and 5p15.31-p15.1 (8,520,001-18,080,000, child 2-pathogenic). One duplication at 6p25.3-p24.3 (1-10,420,000) was detected and determined as likely pathogenic. The chromosomal breakpoints in family 3 were successfully identified by WGS. Conclusion: Some critical genes that were supposed to be causative of the symptoms were identified. Relevant region in 5p deletion syndrome was redefined, and the chr5:7,700,000-8,740,000 region was supposed to be responsible for the cat-like cry. The great potential of WGS in detecting chromosomal translocations was demonstrated. Our findings may pave the way for further research on the prevention, diagnosis, and treatment of related diseases.